No Difference in Return to Duty Between Minimally Invasive, Percutaneous Achilles Tendon Repair and Nonoperative Functional Rehabilitation in Active Duty Military Members. Issue 2 (April 2022) - Tropf, Jordan; Piscoya, Andres S.; Lundy, Alexander; Nelson, Sarah; Eckel, Tobin T.
Category: Sports; Trauma; Other Introduction/Purpose: Achilles tendon ruptures are common injuries in the active duty US military population. Timely rehabilitation has critical importance in force readiness. There remains debate about optimal treatment of Achilles tendon ruptures. Recent studies have found decreased risk of rerupture but increased complication rates with operative management, with similar times to full recovery. The development of a minimally invasive, percutaneous Achilles tendon technique has shown lower rates of wound complications than open management, with similar re-rupture rates. However, there exists no comparative studies between the percutaneous, minimally invasive Achilles tendon surgery and nonoperative management. This was a retrospective cohort study comparing the results of the Percutaneous Achilles Repair System (PARS) and nonoperative management in the active duty military population. Methods: All Achilles tendon injuries in active duty patients were identified using the MHS system M2 from January 1, 2016 to December 31, 2020. Inclusion and exclusion criteria were applied and charts were reviewed. Demographic and treatment information were recorded. Time to return to duty, rerupture, complications, and deep vein thrombosis (DVT) were recorded and compared between each cohort. 47 patients met inclusion criteria with an average age of 38.7 years. There were 23 patients in the percutaneous operative group and 24 patients in the nonoperative group. Patients in the nonoperative group underwent regular functional rehabilitation supervised by a licensed physical therapist under the tri-service rehabilitation guidelines, based on the Willits protocol for nonoperative management (2010). 2 patients failed nonoperative management and underwent open Achilles reconstruction. They were excluded from the time to return to duty analysis. Demographics were described. There were no significant differences in group demographics. Results: There was no difference in time to return to duty in the nonoperative and percutaneous Achilles tendon repair (160.5 days, 5.35 months vs 161.7 days, 5.39 months) cohorts (p=0.47). No patient failed to return to duty due to treatment of an Achilles rupture. There were no DVTs in either group. There was 1 wound complication (infection) (4.3%) and 3 instances of postoperative paresthesias (2 sural, 1 peroneal) 13% in the operative cohort. 2 patients failed nonoperative management (reruptured Achilles tendon) and underwent open reconstruction with flexor halluces longus augmentation (8%). The operative cohort had a higher rate of complications (17.3% vs 8.3%, p=0.42, OR=2.11, CI= (0.34, 12.86)), although this was not statistically significant. There were no reruptures in the operative cohort. Conclusion: There was no difference in time to return to duty in the nonoperative and percutaneous Achilles tendon repairs. There was a higher rate of reruptures in the nonoperative group. Percutaneous operative treatment had a higher risk of complications. There were no failures in the operative cohort. The final decision on management of acute Achilles tendon ruptures should be based on specific patient factors and shared decision to return military members back to duty as quickly as possible. Prospective or well designed randomized controlled trials are necessary in the future to better delineate outcomes between nonoperative and percutaneous Achilles rupture management.